Spectral and generation properties of new coumarins – benzopyrylium derivatives - Anufrik, Slavamir S.; Tarkovsky, Vikentiy V.; Anuchin, Sergey N. (Journal of the Belarusian State University. Physics, 2022)
The spectral and generation parameters of coumarins, benzopyrylium derivatives, in ethanol and acetonitrile under coherent excitation were studied. It was found that the absorption spectra of the investigated compounds contain several maxima and the structuredness of the spectra is associated with their bichromophoric structure. It is shown that these organic dyes are bichromophoric compounds. It is noted that the nature of the substituents in positions 6 and 7 of the coumarin base and positions 6′ and 7′ of the benzopyrylium core determines their spectral-luminescent and lasing properties. It is demonstrated that the presence of substituents in certain positions of the coumarin base and the benzopyrylium core changes the conformation of the molecule and, accordingly, the dipole moments and oscillator strengths of the transition. The generation ability of coumarins of this class manifests itself only in the presence of the strongest donor substituents (for example, Et2N and OH) in position 7, and sufficiently strong acceptors in positions 6′ and 7′. Lasing was obtained in the spectral region of 730 –740 nm on dyes – benzopyrylium derivatives.